The first thousand years a global history of Christianity - Wilken, Robert Louis, 1936- (New Haven : Yale University Press, 2012)
"A narrative account of the history of Christianity from its beginning to the end of the first millennium. The principal theme is the slow drama of the building of a Christian civilization. A major theme is the mission of Christians among different peoples in many regions of the ancient world: Ethiopia, Nubia, Armenia, Georgia, Persia, central Asia, India, China as well as among the Germanic peoples of northern Europe and the Slavic peoples in the Balkans and Russia. The rise and spread of Islam is integral to the story"--
Beginning in Jerusalem -- Ephesus, Rome, and Edessa : the spread of Christianity -- The making of a Christian community -- Divisions within -- Constructing a catacomb -- A learned faith : Origen of Alexandria -- Persecution : Cyprian of Carthage -- A Christian emperor : Constantine -- The Council of Nicaea and the Christian creed -- Monasticism -- A Christian Jerusalem -- Emperor Julian, the Jews, and Christians -- Bishop and Emperor : Ambrose and Theodosius -- Architecture and art -- Music and worship -- The sick, the aged, and the poor : the birth of hospitals -- The bishop of Rome as pope -- An ordered Christian society : canon law -- Augustine of Hippo -- The great controversy over Christ -- Egypt and the Copts; Nubia -- African Zion : Ethiopia -- Syriac-speaking Christians : the Church of the East -- Armenia and Georgia -- Central Asia, China, and India -- A Christian empire : Justinian -- New beginnings in the West -- Latin Christianity spreads north -- The SACKING of Jerusalem : more controversy over Christ -- No God but God : the rise of Islam -- Images and the making of Byzantium -- Arabic-speaking Christians -- Christians under Islam : Egypt and North Africa -- Christians under Islam : Spain -- An emperor in the West : Charlemagne -- Christianity among the Slavs.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Church history -- Primitive and early church, ca. 30-600.; Church history -- Middle Ages, 600-1500.; RELIGION / Christian Church / History; RELIGION / Christianity / History; Electronic books